A Single Point Mutation in the Gene Encoding Gb3/CD77 Synthase Causes a Rare Inherited Polyagglutination Syndrome - Suchanowska, Anna (American Society for Biochemistry and Molecular Biology, 2012)
Rare polyagglutinable NOR erythrocytes contain three unique globoside (Gb4Cer) derivatives, NOR1, NOR(int), and NOR2, in which Gal(α1–4), GalNAc(β1–3)Gal(α1–4), and Gal(α1–4)GalNAc(β1–3)Gal(α1–4), respectively, are linked to the terminal GalNAc residue of Gb4Cer. NOR1 and NOR2, which both terminate with a Gal(α1–4)GalNAc- sequence, react with anti-NOR antibodies commonly present in human sera. While searching for an enzyme responsible for the biosynthesis of Gal(α1–4)GalNAc, we identified a mutation in the A4GALT gene encoding Gb3/CD77 synthase (α1,4-galactosyltransferase). Fourteen NOR-positive donors were heterozygous for the C>G mutation at position 631 of the open reading frame of the A4GALT gene, whereas 495 NOR-negative donors were homozygous for C at this position. The enzyme encoded by the mutated gene contains glutamic acid instead of glutamine at position 211 (substitution Q211E). To determine whether this mutation could change the enzyme specificity, we transfected a teratocarcinoma cell line (2102Ep) with vectors encoding the consensus Gb3/CD77 synthase and Gb3/CD77 synthase with Glu at position 211. The cellular glycolipids produced by these cells were analyzed by flow cytometry, high-performance thin-layer chromatography, enzymatic degradation, and MALDI-TOF mass spectrometry. Cells transfected with either vector expressed the P1 blood group antigen, which was absent from untransfected cells. Cells transfected with the vector encoding the Gb3/CD77 synthase with Glu at position 211 expressed both P1 and NOR antigens. Collectively, these results suggest that the C631G mutation alters the acceptor specificity of Gb3/CD77 synthase, rendering it able to catalyze synthesis of the Gal(α1–4)Gal and Gal(α1–4)GalNAc moieties.